ISLAMISASI ILMU PENGETAHUAN - Moh Hafid (JURNAL HAKAM, 2021)
An idea emerged to bring together the physical and metaphysical realms. A new science that was modern but still religious in nature and based on monotheism was known as the "Islamization of Science." This idea became popular since its inception, namely in the early '80s. This idea was first coined by Syed Naquib al-Attas and popularized by Ismail Ragi al-Faruqi, which is still being discussed among Muslims. This is why the author is interested in studying further about Islam and science, the history and goals of Islamization and Islamization of science. Islamization of science means the liberation of knowledge from interpretations based on secular ideologies and from the meanings and expressions of earthly humans. With the Islamization of science, Muslims will be freed from the shackles of things contrary to Islam so that harmony and peace will arise in themselves, according to their nature. To recast the entire treasure trove of knowledge according to Islamic perspective and match his ideas on the Islamization of knowledge, al-Faruqi put the "principle of monotheism" as the framework of thought, methodology, and way of life of Islam.